Neanderthal: The Strange Saga of the Minnesota Iceman by Bernard Heuvelmans, translated by Paul LeBlond, with Afterword by Loren Coleman - Meldrum, Jeffrey (Journal of Scientific Exploration, 2016)
The story of the Minnesota Iceman, the alleged corpse of an unknown hominid, might be conflated by some today, with a more recent iteration on this theme—the claim by charlatans Rick Dyer and Matt Wheaton to have recovered the corpse of a shot and dispatched Bigfoot and their sophomoric attempt to entomb it in a block of ice. In fact, there was a second attempt by Dyer (what is the adage?—“Fool me once, shame on you; fool me twice . . . ”). In the second more notorious incident, Dyer claims to have shot the unfortunate specimen himself outside of Austin, Texas. Eventually, the supposedly taxidermied skin was stuffed and displayed in a crude plywood coffin placed in a garishly decorated trailer, while the corpse itself was reportedly sequestered in a secret lab facility, being examined by unnamed specialists. The resemblance between these tales and the Minnesota Iceman largely ends there, at least as far as the lead in goes. In 1968, the Iceman incident involved a credentialed scientist, Bernard Heuvelmans, and a renowned naturalist, Ivan T. Sanderson, who examined Frank Hansen’s exhibit extensively in December 1968. Beyond that, the similarity in outcomes remains an open question. For decades, those Anglophones interested in the saga of the Iceman were left to rely largely on the popular papers by Sanderson in Argosy (May 1969), a men’s adventure magazine. Additionally, there were the secondhand insights offered by authors of books touching upon the subject, most notably Dr. John Napier’s Bigfoot: The Yeti and Sasquatch in Myth and Reality, one of few primatologists who gave the question of unknown primates a semblance of objective consideration. It was Heuvelmans’ perhaps rash rush to publish a scientific report of the discovery and examination in March 1969, in the Bulletin of the Royal Institute of Natural Science in Belgium, which precipitated much publicity for the Iceman. However, his original report remained inaccessible to most English speakers. Heuvelmans’ in-depth account of events and descriptions of the Iceman was published in 1974 as the second part of a joint effort with Russian Historian (and hominologist) Boris Porshnev, entitled Neanderthal Man Is Still Alive.